Protocol for a prospective collaborative systematic review and meta-analysis of individual patient data from randomised controlled trials of vasoactive drugs in acute stroke: the Blood pressure in Acute Stroke Collaboration, stage-3 (BASC-3) - Sandset, Else Charlotte; Sanossian, Nerses; Woodhouse, Lisa J.; Anderson, Craig; Berge, Eivind; Lees, Kennedy R.; Potter, John F.; Robinson, Thompson G.; Sprigg, Nikola; Wardlow, Joanna M.; Bath, Philip M.W. (SAGE, 2018)
Rationale Despite several large clinical trials assessing blood pressure lowering in acute stroke, equipoise remains, particularly for ischaemic stroke. The ‘Blood pressure in Acute Stroke Collaboration’ (BASC) commenced in the mid 1990s focusing on systematic reviews and meta-analysis of blood pressure lowering in acute stroke. From the start, BASC planned to assess safety and efficacy of blood pressure lowering in acute stroke using individual patient data. Aims To determine the optimal management of blood pressure in patients with acute stroke, encompassing both intracerebral haemorrhage and ischaemic stroke. Secondary aims are to assess which clinical and therapeutic factors may alter the optimal management of high blood pressure in patients with acute stroke and to assess the effect of vasoactive treatments on haemodynamic variables. Methods and design Individual patient data from randomised controlled trials of blood pressure management in participants with ischaemic stroke and/or intracerebral haemorrhage enrolled during the ultra-acute (pre-hospital), hyper-acute (<6 hours), acute (<48 hours) and sub-acute (<168 hours) phases of stroke. Study outcomes The primary effect variable will be functional outcome defined by the ordinal distribution of the modified Rankin Scale; analyses will also be carried out in prespecified subgroups to assess the modifying effects of stroke-related and pre-stroke patient characteristics. Key secondary variables will include clinical, haemodynamic and neuroradiological variables; safety variables will comprise death and serious adverse events. Discussion Study questions will be addressed in stages, according to the protocol, before integrating these into a final overreaching analysis. We invite eligible trials to join the collaboration.